Computational thinking analysis in solving elementary school AKM numeracy problems - Nunuk Nurcahyani Adiyastuti; Sutama Sutama; Yulia Maftuhah Hidayati (Universitas PGRI Madiun, 2024)
Computational thinking skills play an important role in developing students' critical and logical thinking skills in solving problems. The purpose of this study was to explore computational thinking skills in all aspects (decomposition, abstraction, pattern recognition and algorithm) of grade IV Special Programme Learning Primary School in urban areas in solving AKM numeracy problems. Data collection was carried out through written tests, interviews, and documentation. The method applied in this study was qualitative with a case study design. The data validity test used was the source and method triangulation technique. In the data analysis technique, qualitative analysis techniques were used, namely data reduction, data presentation and drawing conclusions. The results of the study showed that the computational thinking ability of students can be categorized into complete and uncomplete. Learners with the complete category fulfill all four indicators of computational thinking, namely being able to decompose complex problems into simple ones (decomposition), being able to formulate important information (abstraction), identifying patterns (pattern recognition) and being able to compile systematic logical steps (algorithms). Learners with uncomplete abilities have not fulfilled the four indicators of computational thinking, namely namely some learners can identify relevant information (decomposition, abstraction), recognize patterns (pattern recognition) but most have not been able to design problem solving steps systematically (algorithms) and there are also some learners who have not been able to understand the problem at all and analyze problem solving.